A B-spline Quasi-interpolation EMD Method for Similarity/Dissimilarity Analysis of DNA Sequences (Journal of Fiber Bioengineering and Informatics, 2015)
A B-spline Quasi-interpolation Empirical Mode Decomposition (BSQI-EMD) method is presented and\rapplied to similarity analysis of DNA sequences. The B-spline quasi-interpolation is used to approximate\rthe extrema envelopes during the Intrinsic Mode Function (IMF) sifting process. The BSQI-EMD\rmethod is simple, easy to implement, and does not require solving any linear system of equations. Then\rwe implement the classic EMD method and our method respectively. This work verifies our method's\rsuitability and better performance for similarity/dissimilarity analysis among the coding sequences of\rthe first exon of \u03b2-globin gene of ten different species.
Keywords: EMD; IMFs; B-spline Quasi-interpolation; Similarity/Dissimilarity Analysis; DNA Sequences